2020
DOI: 10.3390/ijms21031135
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Melatonin in Assisted Reproductive Technology and Ovarian Aging

Abstract: Melatonin is probably produced in all cells but is only secreted by the pineal gland. The pineal secretion of melatonin is determined by the light-dark cycle, and it is only released at night. Melatonin regulates biological rhythms via its receptors located in the suprachiasmatic nuclei of the hypothalamus. Melatonin also has strong antioxidant activities to scavenge free radicals such as reactive oxygen species (ROS). The direct free radical scavenging actions are receptor independent. ROS play an important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
111
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(114 citation statements)
references
References 75 publications
1
111
0
2
Order By: Relevance
“…There were some possible explanations to our results as follows: 1) MT receptors (MTR) are present in granulosa cells, oocytes and embryos [14,20,21], which laid foundation for MT's function. 2) MT is amphiphilic, and it can easily pass through cell membranes [4]. 3) Both MT and its metabolites are terminal stable antioxidant, will not act as an oxidant in any case [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…There were some possible explanations to our results as follows: 1) MT receptors (MTR) are present in granulosa cells, oocytes and embryos [14,20,21], which laid foundation for MT's function. 2) MT is amphiphilic, and it can easily pass through cell membranes [4]. 3) Both MT and its metabolites are terminal stable antioxidant, will not act as an oxidant in any case [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…A few reports have shown that melatonin exerts protective effects in several experimental models of PD [ 200 , 201 , 202 , 203 ]. For a long time, a chemical, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), has been used as a tool to induce PD in animal models [ 204 ], since it is a neurotoxic and psychoactive agent [ 205 ].…”
Section: Translational Applications Of Melatonin Against Nddsmentioning
confidence: 99%
“…Some antioxidants (such as MLT and resveratrol) have been shown to counteract the negative effects of cryopreservation on the quantity and quality of OTs, probably through the enhancement of free radical scavenging mechanisms in the follicles ( Tarín et al, 2002 ; Rocha et al, 2018 ; Olcese, 2020 ). Therefore, antioxidants are required for elimination of ROS ( Tamura et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin (N-acetyl-5-methoxytryptamine), one of the most well-studied molecules in recent years, is mainly synthesized and secreted by pineal organ of animal and human. It acts as an antioxidant in several reproductive organs and can directly scavenge a variety of free radicals ( Reiter et al, 2016 ; Tamura et al, 2020 ). It also functions to upregulate antioxidant protein expression and to protect against oxidant-mediated damage in many cryopreserved sperm/tissues (human sperm and ovary) ( Li et al, 2009 ; Wang et al, 2012 ; Gao et al, 2016 ; Deng et al, 2017 ; Goodarzi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%